Peningkatan Fungsi Kognitif Lansia melalui Senam Otak di Posbindu RT 03 Desa Anjir Serapat Muara 1 - Ica Lisnawati; Meti Agustini; Nor Afni Oktavia; Muhammad Anwari; Abdus Salam; Yulia Shafira (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Aging in the elderly is often accompanied by cognitive decline that can progress to dementia, requiring non-pharmacological interventions such as brain gym. This activity aimed to improve cognitive function among the elderly through structured brain gym at Posbindu RT 03, Anjir Serapat Muara 1, using a participatory approach combining health education with practice assistance for 30 elderly participants. Activities included health screenings, pre-tests, educational material, demonstrations, and a 15-minute brain gym practice, with cognitive function measured using MMSE and analyzed using the Paired Samples T-Test. Before the intervention, 15 respondents (50%) had mild and 15 (50%) severe impairment; afterward, 6 (20%) achieved normal function, 19 (63.3%) mild impairment, and only 5 (16.7%) remained severe, since rhythmic movements in brain gym trigger cerebral circulation and oxygenation, optimizing motor coordination and cognition. Thus, brain gym significantly improved cognitive function among elderly with dementia at the service location (p = 0.000 0.05).